Relative efficacy of chlorothalonil for controlling leaf blight (Colletotrichum gloeosporioides) of scented geranium (Pelargonium graveolens) - KALRA, A; PARAMESWARAN, T N; RAVINDRA, N S (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted duriog 1992-93 at Bangalore on the bioefficacy of chlorothalonil for controlling leafblight of geranium (Pelargonium graveolens (L.) Herit.) caused by Colletotrichum gloeosporiodes Penz. thechlorothalonil sprayed plots effectively reduced the disease intensity and gave on an average 242 and 192% greateryields of herbage and essential oil, respectively, compared with the unsprayed plots and it was at par with captafol sprayedplots in both the years. Chlorothalonil though found effective against Collelolrichum gloeosporiodes was not economicalas captafol because of its higher cost.